PENINGKATAN KEMAMPUAN BINA DIRI MENGGOSOK GIGI MELALUI TEKNIK MODELLING PADA ANAK TUNAGRAHITA RINGAN KELAS IV DI SLB ARNADYA - Maharani, Bulan Nur; Usman, Usman; Pristiwaluyo, Triyanto (JURNAL ORTO DIDAKTIKA, 2025)
This research examines the ability to brush teeth in a class IV mildly mentally retarded child at SLB Arnadya. The aim of this research was to find out whether there was an increase in the ability to brush teeth through the application of modeling techniques in class IV mildly mentally retarded children at SLB Arnadya. This research approach is a quantitative approach with descriptive research type. The subject in this research was a child with mild mental retardation in class IV at SLB Arnadya whose initials were F. The data collection technique used was a tooth brushing action test. Data analysis uses test results before and after treatment, describing test results before and after treatment. The results obtained from this research are: 1) The ability to brush the teeth of a class IV mentally retarded child at SLB Arnadya before the application of modeling techniques was in the incapable category; 2) The ability to brush the teeth of a class IV mentally retarded child at SLB Arnadya after applying the modeling technique is in the very capable category; 3) There was an increase in the ability to brush teeth in a class IV mentally retarded child at SLB Arnadya through the application of modeling techniques from the less able category to the very capable category. Thus, the child's abilities after being given treatment increase and are better than before being given treatment.